Pengaruh Variasi Temperatur Perlakuan Panas dan Media Pendingin Terhadap Sifat Mekanis dan Mikrostruktur Aluminium 2024 - Yudhi Chandra Dwiaji (Journal of Applied Mechanical Engineering and Renewable Energy, 2022)
Aluminum alloys 2024 is a kind of metal that enjoys a few upper hands over different sorts of metals. Aluminum composite 2024 is utilized in the common and military airplane industry, to be specific in the skin part of the airplane. Working on the nature of this aluminum amalgam should be possible through heat treatment. To work on the nature of the 2024 aluminum alloys, an intensity therapy process is completed. This study was led to decide the hardness esteem in aluminum materials in 2024 when going through heat treatment. This test was completed at the Machining Studio of PT. GMF Air Asia. utilizing hardness test hardware subsequent to being exposed to warm treatment. The example to be tried, specifically aluminum sheet 2024 thickness 1.6mm with a size of 30 cm x 20 cm. In the warming system for aluminum 2024, it is conveyed outby embedding examples into the warming kitchen to a temperature of 400° C and 500° C, and followed by a regulation cycle with a period of 3 - 5 minutes each. After the intensity therapy process, the following system is the cooling system by dunking aluminum 2024 into the oil and watercooling media compartment until the temperature on the example gets back to business as usual. In the wake of cooling, it was gone on with rockwell hardness testing. In this test, 5 information assortment focuses were done on every example with various places. The consequences of rockwell hardness testing before heat treatment were 29.62 HRB. After heat treatment, the most elevated hardness was found in test examples with oil cooling media at a temperature of 500° C, in particular 59.68 HRB. what's more, the least was tracked down in a comparative treatment to water cooling media at a temperature of 500° C, specifically 56.38 HRB